2022
DOI: 10.1021/acs.macromol.2c01529
|View full text |Cite
|
Sign up to set email alerts
|

Combining Green Light-Activated Photoiniferter RAFT Polymerization and RAFT Dispersion Polymerization for Graft Copolymer Assemblies

Abstract: Although reversible addition−fragmentation chain transfer (RAFT) dispersion polymerization-induced self-assembly (PISA) has become one of the most attractive methods for the synthesis block copolymer assemblies, the synthesis of well-defined graft copolymer assemblies has rarely been reported. Herein, multifunctional macro-RAFT agents with well-defined structures were synthesized by green light-activated photoiniferter RAFT polymerization and subsequently used in RAFT dispersion polymerization for the synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 91 publications
1
12
0
Order By: Relevance
“…With the further increase of conversion from 67 to 75%, lamellar structures eventually evolved into vesicular structures as indicated in Figure c,d. Similar results were also found in the work of Tan and co-workers, by using a poly­(poly­(ethylene glycol) methyl ether methacrylate)- co -poly­(2-(2-(nbutyltrithiocarbonate)­propionate)­ethyl methacrylate) (PPEGMA m - co -BTPEMA n ) macro-CTA with a random sequence of backbone …”
Section: Effect Of the Backbone Sequence Of Macro-ctas On Their Pisa ...supporting
confidence: 87%
See 2 more Smart Citations
“…With the further increase of conversion from 67 to 75%, lamellar structures eventually evolved into vesicular structures as indicated in Figure c,d. Similar results were also found in the work of Tan and co-workers, by using a poly­(poly­(ethylene glycol) methyl ether methacrylate)- co -poly­(2-(2-(nbutyltrithiocarbonate)­propionate)­ethyl methacrylate) (PPEGMA m - co -BTPEMA n ) macro-CTA with a random sequence of backbone …”
Section: Effect Of the Backbone Sequence Of Macro-ctas On Their Pisa ...supporting
confidence: 87%
“…Similar results were also found in the work of Tan and coworkers, by using a poly(poly(ethylene glycol) methyl ether methacrylate)-co-poly(2-(2-(nbutyltrithiocarbonate)propionate)ethyl methacrylate) (PPEGMA m -co-BTPEMA n ) macro-CTA with a random sequence of backbone. 55 In contrast, the PISA behaviors of P(NB-g-PEG 45 ) m -b-P(NB-CTA) n with a block sequence were investigated. For the morphology evolutions of P(NB-g-PEG 45 ) 20 -b-P(NB-CTA) 40 mediated RAFT dispersion polymerization , the spherical micelles with a growing size from the initial 35 nm of the seeded micelles to 59 nm were observed before 53% St monomer conversion, as shown in Figures 5a−c and S8).…”
Section: Macro-ctas On Their Pisa Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 55,63‐64 ] To further control the distribution of side chains, we combined photoiniferter RAFT polymerization and RAFT dispersion polymerization to synthesize a series of well‐defined graft copolymer assemblies. [ 65 ] Hong et al . [ 66 ] explored the first topological effect of cyclic and linear macro‐RAFT agents under RAFT‐PISA conditions, and it was found that the use of cyclic macro‐RAFT agent led to a delayed morphological transition as compared to its linear analog.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Another significant advantage of PISA is that block copolymer nanoparticles with various morphologies could be directly produced at high solids. A series of PPEGMA 14.9 -PAMA n nanoparticles were then prepared by RAFT emulsion polymerization of AMA (15% w/w) and characterized by transmission electron microscopy (TEM). Similar to other aqueous PISA formulations, , morphologies of these PPEGMA 14.9 -PAMA n nanoparticles were also sensitive to the volume ratio of two blocks.…”
mentioning
confidence: 99%